Whole-Exome Sequencing in Nine Monozygotic Discordant Twins. (18th December 2015) - Zhang, Rong; Thiele, Holger; Bartmann, Peter; Hilger, Alina C.; Berg, Christoph; Herberg, Ulrike; Klingmüller, Dietrich; Nürnberg, Peter; Ludwig, Michael; Reutter, Heiko
Abstract : By definition, monozygotic (MZ) twins carry an identical set of genetic information. The observation of early post-twinning mutational events was shown to cause phenotypic discordance among MZ twin pairs. These mutational events comprise genomic alterations at different scales, ranging from single nucleotide changes to larger copy-number variations (CNVs) of varying sizes, as well as epigenetic changes. Here, we performed whole-exome sequencing (WES) in nine discordant MZ twins to identify somatic mutational events in the affected twin that might exert a dominant negative effect. Five of these MZ twin pairs were discordant for congenital heart defects (CHD), two for endocrine disorders, one for omphalocele, and one for congenital diaphragmatic hernia (CDH). Analysis of WES data from all nine MZ twin pairs using the de novo probability tool DeNovoGear detected only one apparent de novo variation in TMPRSS13 in one of the CHD-affected twins. Analysis of WES data from all nine MZ twin pairs by using standard filter criteria without the de novo probability tool DeNovoGear revealed a total of 6, 657 variations in which both the twin pairs differed. After filtering for variations only present in the affected twins and absent in in-house controls, 722 variations remained. Visual inspection for read quality decreased this number to 12, present only in the affected twin. However, Sanger sequencing of the overall 13 variations failed to confirm the variation in the affected twin. These results suggest that somatic mutational events in coding regions do not seem to play a major role in the phenotypic expression of MZ discordant twin pairs.